Think like a man - Merryman, Keith; Packer, Will; Newman, David A.; Story, Tim; Union, Gabrielle; Brown, Chris, 1989-; Henson, Taraji P.; Ealy, Michael; Hart, Kevin, 1979-; Harvey, Steve, 1956- (Columbia ; Sony Pictures Home Entertainment, 2012)
Based on Steve Harvey's relationship self-help book, Act Like a Lady, Think Like a Man. Four women have decided to take the advice in Harvey's book and use the recommendations to get their men on track. When the men discover this, they try to turn the tables on their women.